Relationship between Soft Skills and Academic Outcomes in Higher Education: Evidence from Undergraduate Management Students - Ashot G. Mirzoyan; Irina P. Suslova; Angelina V. Govorova (Вопросы образования)
The article considers the problem of development and assessment of competencies in higher educational institutions. The relationship between the grades for academic disciplines and the level of competence development of undergraduate students in the direction of “Management” of the Faculty of Economics of Lomonosov Moscow State University is investigated. The analysis uses a multiple regression model, logistic regression, ordinal logistic regression and hierarchical clustering. According to the simulation results, it is shown that the numerical abilities of students are positively associated with grades in 22 subjects. The Leadership competence is positively associated with grades in three subjects, persuasion skills – in nine, analytical abilities – in seven. Numerical abilities and the competence of “Persuasion” are positively associated with the average grade of students in all subjects. At the same time, decision–making skills are negatively associated with assessments in nine disciplines, and communication skills - in five disciplines, which may be explained by the peculiarity of the assessment tools used. In 14 cases out of 26, competencies predict the grades students receive better than numerical abilities. In order to bridge the gap between approaches to assessment within academic disciplines and approaches common among employers, recommendations are proposed for making changes to the formats of assessment tools and changes in the structure of the template of working disciplines.